(untitled) (The Macau Ricci Institute Journal, 2023)
The following analysis presents Catholicism-inspired meditation on the Chinese characters for self-examination. It is a Catholic viewpoint, which may assist 21st-century Christians and non-Christians in their spiritual struggles. The goal of this analysis is to show that Chinese characters can tell us that the spiritual struggle to improve (ἄσκησις, áskēsis, in Greek) is inherent to the human condition. In that sense, we can see that Chinese tradition is not as foreign to Christian tradition as most may think. Keywords: I, self, China, Catholicism, Chinese characters, Matteo Ricci, Personalism, Erasmus of Rotterdam, good, evil.